Corpo della frase e periferia sinistra nella frase toscana antica - Righi, Federico (Verbum – Analecta Neolatina, 2012)
This paper focuses on a possible reinterpretation of the syntactic structure of the Old Italian sentence: some dislocations of the finite verb (V) and of its arguments could be due not to purely syntactic but also to pragmatic reasons, namely they’re realized in order to give a specific interpretation to the sentence as a whole. Attention will be especially given to OV and V1 orders, resorting to the data drawn from some Medieval Italian texts (in particular, the Novellino and what is known as the Tristano Riccardiano). The article concludes with some remarks about the syntax of the clitic forms and some guidelines for the future studies about this topic.